Altered dopamine D3 receptor gene expression in MAM model of schizophrenia is reversed by peripubertal cannabidiol treatment - Stark, Tibor; Di Bartolomeo, Martina; Di Marco, Roberta; Drazanova, Eva; Platania, Chiara Bianca Maria; Iannotti, Fabio Arturo; Ruda-Kucerova, Jana; D'Addario, Claudio; Kratka, Lucie; Pekarik, Vladimir; Piscitelli, Fabiana; Babinska, Zuzana; et al. (Biochemical pharmacology, 2020)
Gestational methylazoxymethanol acetate (MAM) treatment produces offspring with adult phenotype relevant to schizophrenia, including positive- and negative-like symptoms, cognitive deficits, dopaminergic dysfunction, structural and functional abnormalities. Here we show that adult rats prenatally treated with MAM at gestational day 17 display significant increase in dopamine D3 receptor (D3) mRNA expression in prefrontal cortex (PFC), hippocampus and nucleus accumbens, accompanied by increased expression of dopamine D2 receptor (D2) mRNA exclusively in the PFC. Furthermore, a significant change in the blood perfusion at the level of the circle of Willis and hippocampus, paralleled by the enlargement of lateral ventricles, was also detected by magnetic resonance imaging (MRI) techniques. Peripubertal treatment with the non-euphoric phytocannabinoid cannabidiol (30 mg/kg) from postnatal day (PND) 19 to PND 39 was able to reverse in MAM exposed rats: i) the up-regulation of the dopamine D3 receptor mRNA (only partially prevented by haloperidol 0.6 mg/kg/day); and ii) the regional blood flow changes in MAM exposed rats. Molecular modelling predicted that cannabidiol could bind preferentially to dopamine D3 receptor, where it may act as a partial agonist according to conformation of ionic-lock, which is highly conserved in GPCRs. In summary, our results demonstrate that the mRNA expression of both dopamine D2 and D3 receptors is altered in the MAM model; however only the transcript levels of D3 are affected by cannabidiol treatment, likely suggesting that this gene might not only contribute to the schizophrenia symptoms but also represent an unexplored target for the antipsychotic activity of cannabidiol.
Keywords: haloperidol; Models, Molecular; Schizophrenia; potkani Sprague-Dawley; těhotenství; kanabidiol; mozkový krevní oběh; Gene Expression Regulation; Disease Models, Animal; Haloperidol; Puberty; mužské pohlaví; mozek; Molecular Dynamics Simulation; Antipsychotic Agents; magnetická rezonanční tomografie; regulace genové exprese; receptory dopaminu D2; Receptors, Dopamine D3; receptory dopaminu D3; Magnetic Resonance Imaging; Brain; modely nemocí na zvířatech; ženské pohlaví; molekulární modely; zvířata; Pregnancy; zpožděný efekt prenatální expozice; Receptors, Dopamine D2; schizofrenie; antipsychotika; simulace molekulární dynamiky; Cerebrovascular Circulation; Rats, Sprague-Dawley; Arterial Spine Labelling; Methylazoxymethanol Acetate; MAM model; Cannabidiol; Dopamine D3 receptor; puberta; Female; methylazoxymethanolacetát; Prenatal Exposure Delayed Effects; Male; Molecular Dynamics; Animals